Pelvic MRI Evaluation of Polycystic Ovary Syndrome in Reproductive-Age Women: A Cross-Sectional Study - Sakina Naeem, Sumera Tabassum, Ahmed Ali Khan, Arifa Inayat, Samia Saifullah, Mahwash Mansoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder in women of reproductive age characterized by hyperandrogenism, anovulation, and polycystic ovarian morphology. Transvaginal ultrasound is first-line for imaging but may be limited by operator dependence and patient habitus. Pelvic magnetic resonance imaging (MRI) offers high soft-tissue contrast and volumetric assessment. Objective: To comprehensively characterize ovarian morphology using pelvic MRI and assess associations with clinical, hormonal, and metabolic markers. Methods: In this cross-sectional study (July 2022–July 2023), 100 women aged 18–35 years at Sandeman Provincial and Civil Hospitals Quetta meeting Rotterdam criteria underwent evaluation. Age, body mass index, Ferriman–Gallwey score, and fasting hormonal and metabolic assays were recorded. Pelvic MRI measured ovarian volume, follicle number per ovary, stromal area, and stromal-to-ovarian area ratio. Pearson and multivariate regression adjusted for age and BMI assessed relationships. Results: Mean ovarian volume was 12.8 ± 3.5 mL, follicle number per ovary 24.6 ± 7.2, stromal area 3.8 ± 1.1 cm², and stromal-to-ovarian ratio 0.30 ± 0.08. Volume correlated with AMH (r = 0.52), testosterone (r = 0.47), and HOMA-IR (r = 0.30). Follicle number correlated with AMH (r = 0.48) and LH/FSH ratio (r = 0.35). Stromal area correlated with Ferriman–Gallwey score (r = 0.36). Conclusion: Pelvic MRI accurately quantifies ovarian morphology in PCOS and shows strong associations with endocrine and metabolic markers. MRI may complement ultrasound in challenging cases. Keywords: PCOS; pelvic MRI; ovarian volume; stromal hypertrophy; AMH; insulin resistance